Role of miRNAs in regulation of SA-mediated upregulation of genes involved in folate and methionine metabolism in foxtail millet - Hou, Siyu; Men, Yihan; Zhang, Yijuan; Zhao, Kai; Ma, Guifang; Li, Hongying; Han, Yuanhuai; Sun, Zhaoxia (Frontiers in Plant Science, 2022)
The effect of exogenous salicylic acid (SA) on folate metabolism and the related gene regulation mechanisms is still unclear. In this study, the panicle of foxtail millet with different SA concentrations treatment showed that the 5-M-THF content with 6 mM SA treatment was 2.01 times that of the control. An untargeted metabolomic analysis revealed 275 metabolites were enriched in amino acid metabolism pathways. A transcriptome analysis revealed that differentially expressed genes were mainly enriched in the folate metabolic and amino acid synthesis pathways. Moreover, the miRNA-seq analysis revealed that 33 miRNAs and 51 miRNAs targeted 11 and 15 genes related to the folate and amino acid metabolic pathways, respectively. The miRNA‒mRNA interactions related to the folate and methionine metabolic pathways were analysed. The qRT‒PCR results verified 6 miRNA‒mRNA interactions related to the folate and Met metabolic pathways and were consistent with the prediction. In summary, this study lays the theoretical foundation for elucidating the regulatory mechanisms of folate metabolism.